Starfire - Alvarez, Jennifer Lynn (Alvarez, Jennifer Lynn. Guardian Herd, 2014)
"Star is prophesized to become the most powerful winged horse in Anok on his first birthday, but he must first overcome his malformed wings that make him unable to fly and threats from the leaders of the five herds"--